Exploring the influence of submission devices on customer referral creation and receiver reactions in customer referral programs - Wolf, Lukas; Klopfer, Lisa-Marie; Steul-Fischer, Martina; Reinsperger, Maximilian (Journal of Consumer Behaviour, 2024)
Customer referral programs (CRPs) are considered an effective means of customer acquisition through which firms stimulate existing customers to refer services and products to potential new customers. Digitalization and technological developments have led to the common practice of using digital devices like smartphones or laptops to create and submit customer referrals. This is the first study to investigate the influence of submission devices in CRPs from both the sender's and receiver's perspective. Based on four experiments, we demonstrate that smartphone-generated referrals are shorter and less positive than those composed on laptops/PCs. These differences in text length and valence negatively influence receiver responses, leading to lower purchase intentions due to the perceived usefulness of the referral mediating this relationship. Our findings underscore the important role of submission devices for online referral behavior and contribute to the growing body of research on device-mediated consumer behavior, offering crucial insights to optimize the promotion and design of CRPs.<br